Isolation and Characterization of AGAMOUS-Like Genes Associated With Double-Flower Morphogenesis in Kerria japonica (Rosaceae) - Ma, Jiang; Shen, Xiangling; Liu, Zhixiong; Zhang, Dechun; Liu, Wen; Liang, Hongwei; Wang, Yubing; He, Zhengquan; Chen, Faju (Frontiers in Plant Science, 2018)
Double-flower phenotype is more popular and attractive in garden and ornamental plants. There is great interest in exploring the molecular mechanisms underlying the double-flower formation for further breeding and selection. Kerria japonica, a commercial ornamental shrub of the Rosaceae family, is considered an excellent system to determine the mechanisms of morphological alterations, because it naturally has a single-flower form and double-flower variant with homeotic conversion of stamens into petals and carpels into leaf-like carpels. In this study, Sf-KjAG (AGAMOUS homolog of single-flower K. japonica) and Df-KjAG (AGAMOUS homolog of double-flower K. japonica) were isolated and characterized as two AGAMOUS (AG) homologs that occur strictly in single- and double-flower K. japonica, respectively. Our sequence comparison showed that Df-KjAG is derived from ectopic splicing with the insertion of a 2411 bp transposon-like fragment, which might disrupt mRNA accumulation and protein function, into intron 1. Ectopic expression analysis in Arabidopsis revealed that Sf-KjAG is highly conserved in specifying carpel and stamen identities. However, Df-KjAG did not show any putative C-class function in floral development. Moreover, yeast-two-hybrid assays showed that Sf-KjAG can interact with KjAGL2, KjAGL9, and KjAP1, whereas Df-KjAG has lost interactions with these floral identity genes. In addition, loss-of-function of Df-KjAG affected not only its own expression, but also that of other putative floral organ identity genes such as KjAGL2, KjAGL9, KjAP1, KjAP2, KjAP3, and KjPI. In conclusion, our findings suggest that double-flower formation in K. japonica can be attributed to Df-KjAG, which appears to be a mutant produced by the insertion of a transposon-like fragment in the normal AG homolog (Sf-KjAG) of single-flower K. japonica.